1979
DOI: 10.1139/v79-286
|View full text |Cite
|
Sign up to set email alerts
|

Flash photolysis of alkali metal anions in tetrahydrofuran and dimethoxyethane

Abstract: Flash photolysis of K-, Rb-, and Cs-in tetrahydrofuran (THF) produces the corresponding ion-pairs ( K + , e,-), (Rb+, es-), and (Cs', e,-), followed by the regeneration of the parent metal anion, M u . In mixed-metal solutions containing Na and M where M is K, Rb, or Cs, photolysis of Na-also forms the ( M + , e,-) ion-pair and M-, but with the latter then reforming Na-on an extended time scale. Similar results were obtained in dimethoxyethane (DME) at 213 K, but in this case with the initial formation of a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…Our preliminary simulation studies of this system found that Na 0 clearly exists as a TCP in liquid THF, 18 in agreement with experimental interpretations. [1][2][3][4][13][14][15]19 In this work, we explore the molecular nature of the sodium TCP in significantly more detail. We find that the driving force for TCP formation lies in the creation of a tight solvation shell of ∼4 THF oxygens around the partially exposed Na + end of the TCP.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary simulation studies of this system found that Na 0 clearly exists as a TCP in liquid THF, 18 in agreement with experimental interpretations. [1][2][3][4][13][14][15]19 In this work, we explore the molecular nature of the sodium TCP in significantly more detail. We find that the driving force for TCP formation lies in the creation of a tight solvation shell of ∼4 THF oxygens around the partially exposed Na + end of the TCP.…”
Section: Introductionmentioning
confidence: 99%
“…Since we could not independently determine the concentration of the sodide samples, we have assumed that the maximum extinction coefficient of the sodide CTTS transition was the same in all of the solvents as in THF. 47 For reference, the dashed gray curve in this figure shows the spectrum of sodide in THF taken from Gaussian-Lorentzian fit parameters in the literature. 47,67 The figure shows that the absorption spectra of sodide in THF, DME, and DG, all have essentially the same shape and an almost identical maximum wavelength.…”
Section: Background: the Spectroscopy Of Sodide And Its Photopromentioning
confidence: 99%
“…47 For reference, the dashed gray curve in this figure shows the spectrum of sodide in THF taken from Gaussian-Lorentzian fit parameters in the literature. 47,67 The figure shows that the absorption spectra of sodide in THF, DME, and DG, all have essentially the same shape and an almost identical maximum wavelength. The absorption spectrum of sodide in DEE and THF appear to be slightly broader than that in the other solvents, which we have argued previously is likely the result of either a small amount of potasside contamination or scattering from metal oxide particles in the DEE samples.…”
Section: Background: the Spectroscopy Of Sodide And Its Photopromentioning
confidence: 99%
See 2 more Smart Citations